Microdroplet Contaminants: When and Why Superamphiphobic Surfaces Are Not Self-Cleaning - Wong, William S. Y. (ACS Nano, 2020)
[Image: see text] Superamphiphobic surfaces are commonly associated with superior anticontamination and antifouling properties. Visually, this is justified by their ability to easily shed off drops and contaminants. However, on micropillar arrays, tiny droplets are known to remain on pillars’ top faces while the drop advances. This raises the question of whether remnants remain even on nanostructured superamphiphobic surfaces. Are superamphiphobic surfaces really self-cleaning? Here we investigate the presence of microdroplet contaminants on three nanostructured superamphiphobic surfaces. After brief contact with liquids having different volatilities and surface tension (water, ethylene glycol, hexadecane, and an ionic liquid), confocal microscopy reveals a “blanket-like” layer of microdroplets remaining on the surface. It appears that the phenomenon is universal. Notably, when placing subsequent drops onto the contaminated surface, they are still able to roll off. However, adhesion forces can gradually increase by up to 3 times after repeated liquid drop contact. Therefore, we conclude that superamphiphobic surfaces do not warrant self-cleaning and anticontamination capabilities at sub-micrometric length scales.